Mali - Public Expenditure Management and Financial Accountability Review : Public Financial Management Performance Report - World Bank (World Bank, 2012)
The public financial management (PFM) performance assessment in Mali covered all central government revenues and expenditures and the institutions responsible for their management. This means that the assessment covered central government ministries and institutions, along with their de concentrated units in the regions (governors' staff); and autonomous government agencies, of which there were 82 at the time of the assessment. The report consists of: a brief review of Mali's economic situation and the legal and institutional framework for public financial management (section two); a description of the background and the scores attributed to each PEFA performance indicator (section three); and a summary of the Government's reform program and the institutional factors that are likely to impact planning and implementation of reforms (section four).